Carbachol-Induced theta-like oscillations in the rodent brain limbic system: Underlying mechanisms and significance. (December 2018) - Lévesque, Maxime; Avoli, Massimo
Abstract: Theta oscillations (4–12 Hz) represent one of the most prominent physiological oscillatory activity in the mammalian EEG. They are observed in several areas of the hippocampus and in parahippocampal structures. Theta oscillations play important roles in modulating synaptic plasticity during memory and learning; moreover, they are dependent on septal cholinergic inputs. Theta oscillations can be reproduced in vitro in several regions of the temporal lobe in the absence of the septum by employing the cholinergic agonist carbachol (CCh). Here, we review the mechanisms underlying CCh-induced theta oscillations. We address: (i) the ability of temporal lobe neuronal networks to oscillate independently at theta frequency during CCh treatment; (ii) the contribution of intrinsic ionic currents; (iii) the participation of principal cells and interneurons; and (iv) their pharmacological profiles. We also discuss the similarities between CCh-induced theta oscillations and physiological type II theta activity, as well as their roles in synaptic plasticity. Finally, we consider experimental evidence pointing to the contribution of spontaneous and CCh-induced theta activity to epileptiform synchronization.